INTERPROFESSIONAL COLLABORATION IN THE TREATMENT OF PULMONARY TUBERCULOSIS CLIENTS: A CASE STUDY - Lutfian, Lutfian; Asmaningrum, Nurfika (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2024)
Introduction: The complexity of nursing problems arising in patients with pulmonary TB requires professional handling in collaboration between health workers in hospitals. It is used to improve the quality of life and quality of care in patients with TB. However, the application of interprofessional collaboration in some cases of the disease has not been optimalPurpose: Analyze Interprofessional Collaboration in the Care of Pulmonary TB Clients in one of the hospitals in Jember, Indonesia Methods: This study is a case study conducted in one of the hospitals in Jember, Indonesia. The researcher uses the IPC readiness checklist and fills out the IPC implementation evaluation checklist after the patient goes home.Results: The result of this study stated that the implementation of IPC by PPJA, together with other health workers, has not been optimally implemented. In this case, the application of interprofessional collaboration is still not optimal, as evidenced by the results of the IPC implementation checklist assessment, which is still in score categories 1 and 2. There are several obstacles, such as lack of communication between professions, lack of application of PCC and FCC approaches, overlapping roles and responsibilities, stereotypes from one profession to another, and feelings of inferiority to PPJA. PPJA can maximize its role in conducting IPC to improve patient-focused care; thus, the patient quality of life will increase.Conclusion: PPJA can maximize its role in conducting IPC to improve patient-focused care; thus, the patient quality of life will increase.